Analisis Jenis Mikroplastik pada Sedimen Dasar Perairan Pulau Untung Jawa, Kepulauan Seribu, DKI Jakarta - Hafitri, Masitha; Untung Kurnia A, Moch.; Permata, Lintang; MS, Yuniarti (CV. Publikasi Indonesia, 2022)
Microplastics are small plastics (<5 mm) that are difficult to decompose, thus making this material last for a long time. This causes serious problems, especially in the waters. This study aims to quantitatively analyze the sediments found at the bottom of the waters and the types of microplastics as well as the factors that influence their presence in the seabed sediments of Untung Jawa Island, Seribu Islands. The method used is descriptive and observation, wherefrom these methods are determined 4 sampling stations with a depth of 15.4 – 23 m sediment sampling. The result of this research is that the most commonly found microplastics are fragments. The total number of microplastics found was 1324 microplastic particles with characteristic sizes ranging from 15-900µm and various colors. The highest abundance that dominates the number of microplastics based on their size is in the <250 m category with a percentage of 47%. Meanwhile, in the 250 m size category, the frequency was 36% of the total number of microplastics found, then 13% for the 500 m size category, and the remaining 4% frequency for the >750 m size category was found. The results showed that the gravel sand sediment had the highest number of microplastics compared to other sediments. Based on descriptive observations of current data, it is known that there is a relationship between currents and the distribution of microplastics at the research station.